Letramento literário nos anos iniciais do ensino fundamental: concepções, processos de escolarização e práticas docentes em escolas municipais de Catu-Ba - Alves, Fernanda de Santana da Luz (2022)
This work will deal with the conceptions of schooling processes and pedagogical practices of teachers from the beginner years of Elementary School and the working with literary texts and their implications for the development of literary literacy of students from public schools, located in the city of Catu-Ba. Concerns arising from dialogues with municipality teachers about pedagogical practices with literature and difficulties faced in the classroom for the development of literary literacy and consequently children's reading mobilized this research, which takes a look at the schooling processes of the literary text. The general objective is to understand the existing implications between the processes of schooling of literary reading implemented by teachers in the beginner years of Elementary School and the literary literacy of students from three public schools in Catu-Ba. The theoretical foundations are anchored in two axes, namely: reading and literature. From these two theoretical axes, the following categories unfold: conception of reading and reader (FREIRE, 2011; PETIT, 2009; YUNES, 2002, 2009); reading mediation (PETIT, 2009; SANTOS; MARQUES NETO; ROSING, 2009); reader formation (SILVA E., 2009; YUNES, 2002); conception of literature (C NDIDO, 2011);literary reading's schooling (SOARES, 2003, 2011; MIGUEZ, 2003); literacies (STREET, 2014; KLEIMAN, 2008b); literary literacy (COSSON, 2014; PAULINO, 2004, 2010). Based on a qualitative nature, in the methodological field, the study is based on the collaborative research approach (IBIAPINA, 2016). The data were produced in dialogue with the research collaborators, namely, four teachers from municipal schools in Catu, through semi-structured interviews and reflective sessions. The methodology used for the interpretative analysis of the data is anchored in the Discursive Textual Analysis (DTA) (MORAES; GALIAZZI, 2016), which allows the researcher to construct meanings from inferences in the texts and in the contexts in which they were produced. The results allow us to understand that there is, in municipality schools, a concern and a work in progress aimed at the formation of the literary, critical, and autonomous reader in the context of the beginner years of Elementary School. They also indicate that it is still essential to establish a process of permanent education to implement pedagogical proposals based on the different forms and ways of reading literature and articulate what to do with the conceptions of reading, literature, and reader that it is intended to form.